2016
DOI: 10.48550/arxiv.1603.06921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gravitational wave background from Population III binary black holes consistent with cosmic reionization

Kohei Inayoshi,
Kazumi Kashiyama,
Eli Visbal
et al.

Abstract: The recent discovery of the gravitational wave source GW150914 has revealed a coalescing binary black hole (BBH) with masses of ∼ 30 M ⊙ . Previous proposals for the origin of such a massive binary include Population III (PopIII) stars. PopIII stars are efficient producers of BBHs and of a gravitational wave background (GWB) in the 10 − 100 Hz band, and also of ionizing radiation in the early Universe. We quantify the relation between the amplitude of the GWB (Ω gw ) and the electron scattering optical depth (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…This mass retention is further aided by the drastically reduced wind-driven mass loss at zero meatallicity. Finally, the lack of metals has been conjectured to supress the fragmentation of a giant molecular cloud during star formation, increasing the typical mass of population III stars and making these prime progenitor candidates for binary black hole coalescences (Belczynski et al, 2004;Kinugawa et al, 2014;Inayoshi et al, 2016Inayoshi et al, , 2017.…”
Section: Isolated Binaries: Chemically Homogeneous Evolution and Popu...mentioning
confidence: 99%
“…This mass retention is further aided by the drastically reduced wind-driven mass loss at zero meatallicity. Finally, the lack of metals has been conjectured to supress the fragmentation of a giant molecular cloud during star formation, increasing the typical mass of population III stars and making these prime progenitor candidates for binary black hole coalescences (Belczynski et al, 2004;Kinugawa et al, 2014;Inayoshi et al, 2016Inayoshi et al, , 2017.…”
Section: Isolated Binaries: Chemically Homogeneous Evolution and Popu...mentioning
confidence: 99%
“…In these scenarios there would never be a giant phase: both stars would stay within their Roche lobes and eventually form massive BHs, because the cores that collapse would be large. Yet another scenario invokes a Population III origin for massive BH binaries [54][55][56], but semi-analytical models suggest that the probability of GW150914 having formed in the early Universe is ∼ 1% [57].…”
Section: A Black Hole Formation Channelsmentioning
confidence: 99%
“…These merging BH binaries may also be a result of isolated binary evolution in the galactic field due to special modes of stellar evolution and evolution in active galactic nuclei Belczynski et al 2016a;Marchant et al 2016). Some studies also suggested that these LIGO detections are sourced in the first stars (Kinugawa et al 2014(Kinugawa et al , 2016Hartwig et al 2016;Inayoshi et al 2016;Dvorkin et al 2016), cores of massive stars (Reisswig et al 2013;Loeb 2016;Woosley 2016), or dark matter halos comprised of primordial black holes (Bird et al 2016; 1 http://www.ligo.org/ 2 http://www.virgo-gw.eu/ 3 http://gwcenter.icrr.u-tokyo.ac.jp/en/ Clesse & García-Bellido 2016;Sasaki et al 2016).…”
Section: Introductionmentioning
confidence: 99%